Pulsating hydrogen-deficient white dwarfs and pre-white dwarfs observed with TESS : IV. Discovery of two new GW Vir stars : TIC 0403800675 and TIC 1989122424 - Uzundag, Murat (2022)
We present two new GW Vir-type pulsating white dwarf stars, TIC 0403800675 (WD J115727.68-280349.64) and TIC 1989122424 (WD J211738.38-552801.18) discovered in the Transiting Exoplanet Survey Satellite (TESS) photometric data. For both stars, the TESS light curves reveal the presence of oscillations with periods in a narrow range between 400 and 410 s, which are associated with typical gravity (g)-modes. Follow-up ground-based spectroscopy shows that both stars have similar effective temperature (Teff = 110 000 ± 10 000 K) and surface gravity (log g = 7.5 ± 0.5), but different He/C composition (mass fractions): He = 0.75 and C = 0.25 for TIC 0403800675, and He = 0.50 and C = 0.50 for TIC 1989122424. By performing a fit to their spectral energy distributions, we found for both stars radii and luminosities of R = 0.019 ± 0.002 R and log(L/L ) = 1.68+0.15 −0.24, respectively. By employing evolutionary tracks of PG 1159 stars, we find the masses of both stars to be 0.56 ± 0.18 M from the log g-Teff diagram and 0.60+0.11 −0.09 M from the Hertzsprung Russell diagram.